Fabricação de eco-composito com a fibra de lã canina - Silva, Francisco Claudivan da (2012)
The Sustainability has been evidence in the world today; organizations have sought to be more and more into this philosophy in their processes, whether products or attendance. In the present work were manufactured eco-composites with animal fiber (dog wool) that is currently discarded into the environment without any use. The fibers were characterized and made matting (non-woven). The phases of the project were consisted to develop methods and to convert these fibers (booster) blended with polyester resin (matrix) in different proportions (10%, 20% and 30%) at the composite. Were studied fiber characteristics, mechanical properties of the composites, water absorption and scanning electron microscopy. Initially, the fibers were treated with solution of sodium hydroxide of 0.05 mols, and then taken to matting preparing at the textile engineering laboratory - UFRN. The composites were made by compression molding, using an orthophthalic polyester resin as matrix and 1% MEK (methyl ethyl ketone peroxide) as initiator (catalyst). To evaluate the mechanical tests (tensile and flexural) and water absorption were made twelve specimens with dimensions 150x25x3 mm were cut randomly. According to the standard method, tensile tests (ASTM 3039) bending tests (ASTM D790) were performed at the mechanical testing of metals at laboratory UFRN. The results of these tests showed that the composite reinforced with 30% had a better behavior when exposed to tension charge; while on the three points bending test showed that the composite reinforced with 10% had a better behavior. In the water absorption test it was possible to see that the highest absorption happened on the composite reinforced with 30%. In the micrographs, it was possible to see the regions of rupture and behavior of the composite (booster / matrix)